Analisis Naratif Video "Apa Pendapatmu Tentang Disabilitas?" - Permana, Galih Primanda (Jurnal Pewarta Indonesia, 2025)
This study explores the video "Apa Pendapatmu Tentang Disabilitas?" created by UNICEF Indonesia in honor of the International Day of Persons with Disabilities. Using a qualitative approach and narrative analysis, the research delves into how the video’s storytelling shapes public perceptions of individuals with disabilities. The study focuses on elements like emotion, plot, structure, and characters, which collectively convey a strong message of inclusivity. The findings reveal that the video successfully sheds light on the social stigma faced by people with disabilities while showcasing their strength and resilience. By emphasizing narrative coherence and authenticity, the video delivers a powerful and relatable message that encourages viewers to rethink their perspectives. More than just an informational piece, the video emerges as a meaningful tool for challenging discrimination and promoting equality for persons with disabilities. Keywords: narrative analysis, disability, social stigma, storytelling, inclusivity